Flexoelectric Poling of Functionally Graded Ferroelectric Materials. Issue 1 (12th November 2020) - Sharma, Saurav; Kumar, Rajeev; Talha, Mohammad; Vaish, Rahul
Abstract: Flexoelectricity is a phenomenon that can yield an electromechanical coupling in all dielectric materials, whereas piezoelectricity presents itself in specially treated (electrically poled) ferroelectric materials. The present study explores the possibility of achieving electrical poling in a material, purely by mechanical means, by virtue of flexoelectricity and thereby harnessing the potential of coexistence of the two phenomena. A theoretical investigation on a functionally graded ferroelectric material sample of square shape with barium titanate and polyvinylidene fluoride as its constituents is conducted in this direction using isogeometric analysis based computational framework. Applied mechanical load on the material results in varying magnitude of electric field inside the material, which in some fraction of the material reaches a magnitude sufficient enough to yield a permanent poling. Simulation results suggest that it is possible to achieve poling of up to 75% of the material volume. This partially poled material is later considered for its contribution in the total electromechanical coupling of the material. The combination of piezoelectric and flexoelectric effects is found to enhance the equivalent piezoelectric coefficient in converse electromechanical (by up to 90%) coupling while a detrimental effect is observed in direct equivalent piezoelectric coefficient (by up to 89%) due to this combination. Abstract : Theoretical analysis of poling of functionally graded ferroelectric materials, achieved through purely mechanical means by virtue of flexoelectric polarization induced due to mechanical loading, is reported. The result of such poling is the coexistence of both flexoelectric and piezoelectric phenomena in the same sample. Additionally, effective electromechanical coupling due to interplay of these two coexisting phenomena is analyzed.